Isozyme analysis of anaerobic rumen fungi and their relationship to aerobic chytrids - Ho, Y.W.; Khoo, I.Y.S.; Tan, S.G.; Abdullah, N.; Jalaludin, S.; Kudo, H. (Microbiology Societyjournals@microbiologysociety.org, 1994)
Isozymes of 23 cultures of the anaerobic rumen fungi and seven cultures of aerobic chytridiomycete fungi were analysed by PAGE. A total of 14 isozyme loci were successfully typed by PAGE. They were peptidase A and C-1, peptidase A and C-2, peptidase D-1, peptidase D-2, malate dehydrogenase-1, malate dehydrogenase-2, esterase-1, esterase-2, malic enzyme-1, malic enzyme-2, isocitrate dehydrogenase, shikimate dehydrogenase, phosphoglucomutase and 6-phosphogluconate dehydrogenase. Isozyme analysis can be used for studying the genetic relationships among the different anaerobic rumen fungi and the aerobic chytridiomycete fungi and the isozyme characteristics can serve as additional taxonomic criteria in the classification of the anaerobic rumen fungi. A dendrogram based on the isozyme data demonstrated that the anaerobic rumen fungi formed a cluster, indicating a monophyletic group, distinctly separated from the aerobic chytridiomycete fungi. Piromyces communis and P. minutus showed a close relationship but P. spiralis showed a more distant relationship to both P. communis and P. minutus. Piromyces as a whole was more related to Caecomyces than to Neocallimastix. Orpinomyces was also found to be more related to Piromyces and Caecomyces than to Neocallimastix. Orpinomyces intercalaris C 70 from cattle showed large genetic variation from O. joyonii, indicating that it is a different species.